2002
DOI: 10.1088/0022-3727/35/20/328
|View full text |Cite
|
Sign up to set email alerts
|

Barium titanate particle model inquiry through effective permittivity measurements and boundary integral equation method based simulations of the BaTiO3 epoxy resin composite material

Abstract: The heterogeneous mixture properties depend on its constituents' characteristics. We examine the effective permittivity of a two-phase composite material made of epoxy resin host matrix and barium titanate (BaTiO3) filler for different volume fractions in the matrix. The task we undertake consists in finding a model of BaTiO3 particles through the computer simulations executed in PHI3D-electric field calculating package, based on the resolution of the Laplace equation using boundary integral equation method. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, the effective relative permittivity of the composites has been described by models that assume certain particle shapes and volume fractions. It is also known that ceramics and powders of BaTiO 3 show a different dielectric behaviour [33,34,36]. In an experiment reported by Khastgir and Adachi [37], the relative permittivity of a suspension containing 0.137 volume fraction of BaTiO 3 powder in a polydimethylsiloxane (PDMS) resin and crosslinking agent mixture was measured while the resin crosslinked.…”
Section: Relative Permittivity and Stress Reliefmentioning
confidence: 99%
“…In addition, the effective relative permittivity of the composites has been described by models that assume certain particle shapes and volume fractions. It is also known that ceramics and powders of BaTiO 3 show a different dielectric behaviour [33,34,36]. In an experiment reported by Khastgir and Adachi [37], the relative permittivity of a suspension containing 0.137 volume fraction of BaTiO 3 powder in a polydimethylsiloxane (PDMS) resin and crosslinking agent mixture was measured while the resin crosslinked.…”
Section: Relative Permittivity and Stress Reliefmentioning
confidence: 99%
“…13, the mixture was modeled with a cubic lattice of aligned cylinders. 13, the mixture was modeled with a cubic lattice of aligned cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…We carried out experimental verification of the BIEM [8], which showed that it permits us to calculate precisely the effective permittivity of composite materials with regularly shaped inclusions periodically distributed in the host matrix. We also applied the BIEM to the inverse problem, where we predicted globally the grain shape of irregular inclusions based on measurements of the effective characteristics of the composite [9]. In this paper we apply the BIEM to the high voltage problem.…”
Section: Introductionmentioning
confidence: 99%